Static and Fatigue Analysis of Carbon Epoxy Reinforced Composite Leaf Spring - Chatwant Singh Pandher; Brar, Gurinder Singh; Singh, Tejeet (Asian Journal of Engineering and Applied Technology, 2018)
Different fields of mechanical, automobile, aerospace, electronics and communication engineering uses composite material. The automobile industries have shown great interest to change traditional use of steel leaf spring with light weight composite leaf spring with same strength. This research paper presents the general study, fabrication, static and fatigue analysis on carbon epoxy composite leaf spring. A rear leaf spring of Tata Ace (mini truck) made of material EN45 spring steel was selected as practical application. Hand Lay-up technique was used to make a carbon epoxy leaf spring. A single carbon epoxy composite leaf spring is compared with EN45 steel leaf spring. Static test was performed on both steel spring and composite spring from initial load of 1000 N to full load of 5400 N. Results shows that deflection of carbon epoxy composite leaf spring is 14% less as compared to the steel leaf spring which means increase in stiffness. Also fatigue life of composite leaf spring is more than desire 100000 cycles.